2021
DOI: 10.11591/ijeecs.v24.i3.pp1638-1646
|View full text |Cite
|
Sign up to set email alerts
|

Virtual education and student perception of teacher performance in the distance learning environment

Abstract: <span>This article aims to carry out a descriptive analysis of the performance of teachers qualified as researchers, in the distance education environment according to the student's perspective. The results will be a frame of reference for university authorities on the path of continuous improvement of virtual education. When carrying out the research, a general qualification of the teaching performance of 14.20 was determined, established the highest grade equal to 20, it can be indicated that there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Flores-Cáceres et al [29] showed the performance of teachers with respect to virtual education, from which we can draw many very encouraging conclusions regarding the performance of teachers and how they face challenges. The use of digital technology in the teaching-learning process has multiplied in recent years.…”
Section: Resultsmentioning
confidence: 65%
“…Flores-Cáceres et al [29] showed the performance of teachers with respect to virtual education, from which we can draw many very encouraging conclusions regarding the performance of teachers and how they face challenges. The use of digital technology in the teaching-learning process has multiplied in recent years.…”
Section: Resultsmentioning
confidence: 65%
“…This competence helps teachers to find ways to improve practice through permanent reflection, stimulating critical thinking [14]. There is little autonomy of the research teacher and limited acquisition of new skills, which affects their teaching performance [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is urgent to rethink the background of didactic strategies and improve the ways of providing educational services through adequate teaching skills [14], [15], [21]. The role and substantial impact of teaching skills as a facilitator in the student learning process is vital.…”
Section: Introductionmentioning
confidence: 99%